Qualitatively investigating factors contributing to poor health and influencing unhealthy behaviour uptake in deprived areas within the UK - James Stockton; Steve Liu; Jamie P. Halsall; Nadege Ndzogoue (Springer, 2023)
Abstract Background Understanding determinants affecting poor health outcomes and influencing unhealthy behaviours within deprived areas is becoming increasingly common. This study was to investigate the participants' Healthy Eating and Active Living (HEAL) behaviours; their attitudes, thoughts and experiences and the association with the Social Ecological Model (SEM) which could influence health behaviours. Method Data collection occurred in Barnsley an area with high levels of deprivation and health disparities. Information was gathered 97 participants across focus groups and one-to-one interviews. Questions were formulated around HEAL and SEM and questioned origin and maintenance of modifiable behaviours affecting physical activity, diet, and long-term behaviour. Deductive Thematic Analysis (Braun and Clarke in Qual Res Sport Exercise Health 11(4), 589-597, 2019) was used to analyse data. Findings Three themes were identified: Diet and access to unhealthy options, mental health, and attitudes towards government interventions. SEM examined the effectiveness of community level interventions whilst considering the individual responsibility associated with HEAL. Discussion Within research area, attitudes towards HEAL are deeply impacting participants, many of these attitudes originate from childhood transferred from parents. This transference may explain why many deprived areas within England suffer from worse health outcomes, as inherited beliefs result in negative HEAL behavior manifesting in long term health problems. National interventions provided good information; but were hampered by a lack of effective dissemination to the general population. Local interventions often had more success in effectively engaging local people, but participants reported frequent shuttering of local interventions due to funding issues.